PERTANGGUNGJAWABAN HUKUM PELAKU TINDAK PIDANA PEMBUNUHAN YANG DILAKUKAN OLEH SUAMI TERHADAP ISTRI (STUDI KASUS DI PENGADILAN NEGERI PADANGSIDIMPUAN) - Anwar Sulaiman Nasution (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Research is a study on the legal accountability of the perpetrator of the crime of murder committed by the husband against the wife in the Jurisdiction of padangsidimpuan District Court and the causative factor of the crime of murder committed by a husband against his wife in the jurisdiction of padangsidimpuan District Court. This research formulates the issue of how the legal accountability of the perpetrator of the crime of murder committed by the husband against the wife in the Jurisdiction of padangsidimpuan District Court and whether the cause of the crime of murder committed by a husband against his wife in the jurisdiction of Padangsidimpuan District Court. The research that the authors used in the writing of this study is descriptive research which means Then, through inductive and deductive methods, conducted the results of interviews with authors and speakers, as well as conducted field research (library studies) and library studies (field research) on data and documents related to research. Research. The legal liability imposed on a husband who commits the crime of murder against the wife in the Jurisdiction of Padangsidimpuan District Court is only punishable by the fact that there is no weight with the addition of one-third of the threat of the main punishment and the contributing factor of the crime of murder committed by a husband against his own wife is due to the self-esteem as a husband feels harassed which ultimately leads to the quarrel and persecution that resulted in the death of the wife